Comparative study of Leishmania mexicana and Trypanosoma brucei NAD-dependent glycerol-3-phosphate dehydrogenase - Marché, Sylvie; Michels, Paul A.M.; Opperdoes, Fred R. (Molecular and biochemical parasitology, 2000)
The NAD-dependent glycerol-3-phosphate dehydrogenases (G3PDH, EC 1.1.1.8) of Trypanosoma brucei and Leishmania mexicana are thought to have different roles in carbohydrate metabolism. Here the physicochemical and kinetic properties of natural G3PDH from T. brucei with the recombinant homologue of L. mexicana which share 63% positional identity are compared. Despite their supposed different functions in energy metabolism of the parasites the two G3PDHs have remarkably similar properties, including pH optima and K m value for dihydroxyacetone phosphate (DHAP) and NADH in the formation of glycerol 3-phosphate (G3P) and for NAD + and G3P in the reverse reaction. Both enzymes are subject to substrate inhibition by dihydroxyacetone phosphate at concentrations above 0.2 mM and are inhibited by the trypanocidal drugs suramin and melarsen oxide at sub-micromolar concentrations.